Application of bacterioruberin from Arthrobacter sp. isolated from Xinjiang desert to extend the shelf-life of fruits during postharvest storage - Wasim Sajjad; Murad Muhammad; Sayed Muhammad Ata Ullah Shah Bukhari; Sumra Wajid Abbasi; Osama Abdalla Abdelshafy Mohamad; Yong-Hong Liu; Wen-Jun Li (Food Chemistry: Molecular Sciences)
Post-harvest losses and rapid fruit ripening at room temperature are major challenges in preserving fruit quality. This study aimed to reduce such losses by applying a red carotenoid pigment, bacterioruberin extracted from an Arthrobacter sp. The carotenoid was characterized as bacterioruberin and its derivative tetra anhydrous bacterioruberin (λmax 490 nm), and an m/z value of 675 and 742 (M+ 1H)+1. The annotated LIPID MAP demonstrated the presence of over 360 isoprenoids annotated transcripts. The compound exhibited significant antioxidant activity, with an IC50 of 22 μg/mL, iron chelation and antibacterial activities indicating its potential as a natural preservative. When applied to grapes, peaches, and apricots, bacterioruberin (2 %) effectively prevented spoilage for six days at room temperature. Statistical analysis using one-way ANOVA revealed a significant correlation (p = 0.05) between treated and control groups in subjective quality attributes. Computational investigation with phospholipase D and VQ22 motif protein further supported the preservative potential of bacterioruberin.